Efficacy of mebendazole and levamisole, alone or in combination, for soil-transmitted helminthiasis - Ifo Faujiah Sihite; Muhammad Ali; Ayodhia P. Pasaribu; Syahril Pasaribu; Chairuddin P. Lubis (Paediatrica Indonesiana, 2014)
BackgroundThe World Health Organization (WHO) recommends four, single-dose drugs (albendazole, levamisole, mebendazole, and pyrantel pamoate) for management of soilÂtransmitted helminthiasis (STH). Previous studies have shown varied and inconsistent outcomes of these STH treatments.ObjectiveTo compare the efficacy of mebendazole and levamiÂsole, alone or in combination, for the treatment of STH.MethodsAn open randomized controlled trial was conducted in Secanggang, North Sumatera from August to October 2009. School-aged children with STH infection were randomized into three groups. Group I received a single dose of mebendazole (500 mg); group II received a single dose of levamisole (2.5 mg/kg); and group III received a single dose of mebendazole-levamisole combined. Stool samples were collected at baseline, and the 1st, 2nd, 3rd, and 4th weeks after treatment and examined by the Kato-Katz technique. Statistical analyses were Kruskal-Wallis test for cure rate and Analysis of Variance (ANOVA) test for egg reduction rate. ResultsSTH was diagnosed in 197 children with the following parasite species: Ascariasis (96 children, 48.7%), Trichuriasis (58 children, 29.4%), and mixed infection (43 children, 21.8%). We found no hookworm infection in any of our subjects. Groups I and III had significantly higher efficacy (P=0.0001) against STH (egg reduction rate 99.3% and 99.9%; cure rate 92.2% and 98.4%, respectively) at 4th week of treatment.ConclusionA single dose of mebendazole alone and combined with levamisole have better efficacy compared to a single dose of levamisole for the treatment of STH. The highest efficacy of these treatments is noted at the 4th week after drug administration